Cosmological simulations of the same spiral galaxy: the impact of baryonic physics - Nuñez-Castiñeyra, A; Nezri, E; Devriendt, J; Teyssier, R (Oxford University Press, 2020)
The interplay of star formation (SF) and supernova (SN) feedback in galaxy formation is a key element for understanding galaxy evolution. Since these processes occur at small scales, it is necessary to have sub-grid models that recover their evolution and environmental effects at the scales reached by cosmological simulations. In this work, we present the results of the Mochima simulation, where we simulate the same spiral galaxy inhabiting a Milky Way (MW) size halo in a cosmological environment changing the sub-grid models for SN feedback and SF. We test combinations of the Schmidt law and a multifreefall based SF with delayed cooling feedback or mechanical feedback. We reach a resolution of 35 pc in a zoom-in box of 36 Mpc. For this, we use the code RAMSES with the implementation of gas turbulence in time and trace the local hydrodynamical features of the star-forming gas. Finally, we compare the galaxies at redshift 0 with global and interstellar medium observations in the MW and local spiral galaxies. The simulations show successful comparisons with observations. Nevertheless, diverse galactic morphologies are obtained from different numerical implementations. We highlight the importance of detailed modelling of the SF and feedback processes, especially for simulations with a resolution that start to reach scales relevant for molecular cloud physics. Future improvements could alleviate the degeneracies exhibited in our simulated galaxies under different sub-grid models.